Growth Performance and Carcass Characteristics of Broiler Chickens Fed Diets Containing Differently Processed Finger Millet Supplemented with Enzyme - Edache, David O.; John, Samuel O.; Edache, Stephen E.; Emmanuel, Dongtem; Edache, John A. (International Journal of Poultry Science, 2025)
Objectives: The present study was conducted to assess the performance and carcass characteristics of broiler chickens fed diets containing differently processed finger millet meal supplemented with enzymes. Materials and Methods: A total of 150 two-week-old broiler chicks of mixed sexes were randomly allocated to one of four diets in a completely randomized block design. The broiler chicks were allocated one of four diets containing either 0 (Control), uncrushed, roughly crushed, or finely crushed finger millet. The starter diets were isonitrogenous (23% CP) but varied in energy levels from 2,710.00 (Diet A) to 2,726.60 kcal/kg ME (for diets B, C and D respectively). The finisher diet was also isonitrogenous (21% CP) and fed to the birds for 21 days. A total of 37 broiler birds were divided into four groups, each receiving a finisher diet containing 0 (control), uncrushed, roughly crushed and finely crushed finger millet, all (except for control) supplemented with enzyme for 3 weeks. Each diet was replicated thrice with 12 birds each. Some replicates had 13 birds each. Feed and water were made available ad libitum. Results: Feed intake was significantly lower (p<0.05) for birds fed on diets A (0.51), B (0.47) and C (0.46kg) than those fed on diet D (0.60kg/bird). However, weight gain and feed efficiency were similar across treatment groups. Feed cost per kilogram gain was significantly lower in birds fed on diet A (₦ 58.05/bird) than those fed on diets B (₦ 71.18/bird), C (₦ 70.60/bird) and D (₦ 71.18/bird), respectively. No differences were observed in carcass values except for the relative gizzard weight which was significantly higher (p<0.05) for birds fed on diets A (8.76), B (10.71) and C (8.04) than those fed on diet D (6.67%). Conclusion: In order to induce an intake response, finger millet can be fed to broiler chickens in finely ground form but it won’t affect the weight of the carcass organs. When considered collectively, our results showed that crushing the finger millet was unnecessary because it had no significant impact on the birds’ body weight or feed efficiency.